Perkembangan Tradisi Keagamaan Munggahan Kota Bandung Jawa Barat Tahun 1990-2020 - Tata Twin Prehatinia; Widiati Isana (UIN Sunan Gunung Djati Bandung, 2022)
Indonesia is a country with a lot of cultural diversity and is known for its differences. As with the existing traditions in Indonesia, it must have a different diversity in each region. Munggahan tradition is one of the traditions that is still actively carried out by people from the city of Bandung. For them, the Munggahan tradition does not only contain Islamic teachings symbolically, but also contains strong human values so that it can show universal relationships between humans. This article discusses the development of the Munggahan tradition from year to year to the public's perception of the Munggahan tradition itself. Researchers take several ways to convey clearly the perception of the community regarding the Munggahan tradition in Bandung. Researchers conducted interviews with people who already live in Bandung to local community leaders and ustadzah in the area. The munggahan tradition is a tradition that is familiar to our ears when we are in the month of Sya'ban with a reminder that the month of Ramadan will soon be entering.Keyword : Tradisi, Munggahan, Bandung